UPAYA MENINGKATKAN HASIL BELAJAR SENI TEATER MELALUI METODE PEMBELAJARAN TUTOR SEBAYA PADA KELAS X TARI 2 DI SMKN 3 SUKAWATI - I Nyoman Putrayasa; Lady Andly (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
This study aims to determine the improvement of learning outcomes by implementing a peer tutor learning model in class X Dance 2 at SMKN 3 Sukawati. This research method uses Classroom Action Research which is carried out in two cycles with each cycle consisting of planning, action implementation, observation and reflection. The subjects of this study were students of class X Dance 2 at SMKN 3 Sukawati with a total of 25 students. The results showed that there was an increase in the learning outcomes of students in class X Dance 2 SMKN 3 Sukawati from pre- action to cycle I and from cycle I to cycle II as indicated by: a) an increase in the average score in pre-action obtained an average score of 66.2, cycle I obtained an average score of 69.6 and in cycle II with an average score of 75.2.